3D Porous Graphene Films with Large‐Area In‐Plane Exterior Skins. Issue 6 (17th January 2022) - Tay, Roland Yingjie; Li, Hongling; Ng, Zhi Kai; Tsang, Siu Hon; Gao, Wei; Teo, Edwin Hang Tong
Abstract: Construction of macroscopic 3D architectures of graphene is crucial to harness the advantageous properties of planar 2D graphene and to enable integration to many conventional and novel applications. Ideally, the 3D structure of graphene should be free of defects, covalently interconnected, and can be produced at large‐scale. Among various assembly techniques, fabrication using chemical vapor deposition (CVD) enables the production of high‐quality graphene where selection of template is the key that determines its consequent crystalline quality and structural morphology. Herein, a new method is presented to synthesize high‐quality porous graphene film by incorporating an in situ reduction–oxidation cycling treatment to generate micrometer‐sized pores on commercial Ni foil using an all‐CVD process route. Owing to the unique morphological features of the modified Ni template, the graphene film exhibits a holey surface with large‐area exterior skin coverage of >94% and many interconnected ligaments within its porous interior. This extraordinary configuration gives rise to superior in‐plane electrical conductivity despite its low density. In comparison to state‐of‐the‐art materials for electromagnetic interference shielding, this porous graphene film is among the best performing materials with a specific shielding effectiveness of >550 dB cm 3 g −1 and absolute effectiveness of >220 000 dB cm 2 g −1 . Abstract : Synthesis of a new form of 3D graphene film with large‐area exterior skins and interconnected ligaments within its porous interior is demonstrated using an all‐compatible chemical vapor deposition process route. The extraordinary combination of possessing superior in‐plane electron conductivity within a highly porous structure renders such films to exhibit exceptional electromagnetic interference shielding performance.